2017
DOI: 10.5694/mja16.00640
|View full text |Cite
|
Sign up to set email alerts
|

Daily step count and the need for hospital care in subsequent years in a community‐based sample of older Australians

Abstract: More active people require less hospital care, and an achievable extra 4300 steps per day would result in an average of one less day in hospital for each 3 years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Recent analysis from the Hunter Community Study showed that an extra 4,300 steps at baseline, i.e. the difference between the 25 th and 75 th centile of steps in that group of adults over the age of 55 years, resulted in a reduction of 0.29 bed days per year during eight years of follow‐up 11 . If the effect is linear, we could expect an extra 1,000 steps per day to result in reduced requirement for hospital care by one‐third of a day over the subsequent five years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analysis from the Hunter Community Study showed that an extra 4,300 steps at baseline, i.e. the difference between the 25 th and 75 th centile of steps in that group of adults over the age of 55 years, resulted in a reduction of 0.29 bed days per year during eight years of follow‐up 11 . If the effect is linear, we could expect an extra 1,000 steps per day to result in reduced requirement for hospital care by one‐third of a day over the subsequent five years.…”
Section: Resultsmentioning
confidence: 99%
“…the difference between the 25 th and 75 th centile of steps in that group of adults over the age of 55 years, resulted in a reduction of 0.29 bed days per year during eight years of follow-up. 11 If the effect is linear, we could expect an extra 1,000 steps per day to result in reduced requirement for hospital care by one-third of a day over the subsequent five years. As the cost per bed day of hospital admission in the local area health service in 2013 was in the range $1,350 to $1,600, preventing one-third of a bed day in hospital is likely to save more than the cost of our intervention.…”
Section: Recent Analysis From the Hunter Communitymentioning
confidence: 99%
“…PwMS are taking on average 3845 less steps than an inactive NHANES sample with a mean step count per day of 5840 steps. Although it is not possible to accurately predict the effect of a 40% lower daily step count, if continued over a period of years it would seem likely that this substantial decrease in activity will result in an increase in morbidity . Moreover, it is possible that the 40% comparative reduction in steps per day is associated with an increase in disease‐specific symptoms such as fatigue, decreased strength, and gait abnormalities among pwMS.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not possible to accurately predict the effect of a 40% lower daily step count, if continued over a period of years it would seem likely that this substantial decrease in activity will result in an increase in morbidity. 54 Moreover, it is possible that the 40% comparative reduction in steps per day is associated with an increase in diseasespecific symptoms such as fatigue, decreased strength, and gait abnormalities among pwMS. This last question requires further research, to establish the interplay between steps per day and symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the MJA , Ewald and his co‐authors report on the association between increases in daily step counts and the reduced need for hospital care among older Australians 1 . Their findings confirm something international experts widely acknowledge: increasing population levels of physical activity is critical for reducing the global burden of diseases such as coronary heart disease, type 2 diabetes, and breast and colon cancers 2 .…”
mentioning
confidence: 70%